2015
DOI: 10.1021/acs.chemrev.5b00608
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Bioelectronics

Abstract: Nano-bioelectronics represents a rapidly expanding interdisciplinary field that combines nanomaterials with biology and electronics, and in so doing, offers the potentials to overcome existing challenges in bioelectronics. In particular, shrinking electronic transducer dimensions to the nanoscale and making their properties appear more biological can yield significant improvements in the sensitivity and biocompatibility, and thereby open up opportunities in fundamental biology and healthcare. This review empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
507
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(514 citation statements)
references
References 587 publications
(1,144 reference statements)
2
507
0
5
Order By: Relevance
“…field-effect transistor | Debye screening | surface modification | DNA aptamer receptor | polyethylene glycol N anoelectronic biosensors offer broad capabilities for label-free high-sensitivity real-time detection of biological species that are important to both fundamental research and biomedical applications (1)(2)(3)(4)(5)(6). In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…field-effect transistor | Debye screening | surface modification | DNA aptamer receptor | polyethylene glycol N anoelectronic biosensors offer broad capabilities for label-free high-sensitivity real-time detection of biological species that are important to both fundamental research and biomedical applications (1)(2)(3)(4)(5)(6). In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7).…”
mentioning
confidence: 99%
“…In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7). Subsequent studies have demonstrated highly sensitive and in some cases multiplexed detection of key analytes, including protein disease markers (8-10), nucleic acids (11)(12)(13), and viruses (14), as well as detection of protein-protein interactions (8,(15)(16)(17) and enzymatic activity (8).…”
mentioning
confidence: 99%
“…Recent work has reported Bio-FETs based on onedimensional (1D) and two-dimensional (2D) nanostructures such as nanowires, [21][22][23] nanotubes, 24 nanobelts, 25 and nanosheets. [26][27][28][29] Although those nanostructure Bio-FETs possess high 4 sensitivity, both production and application pose major challenges due to significant device-todevice variation and complicated process integration.…”
mentioning
confidence: 99%
“…Differences in methods of communication (electrons versus ions) between traditional electronic devices and biological systems result in a challenge at the interface 7, 8. Silicon nanowire and carbon nanotube transistors integrated with enzymes, antibodies, and lipid bilayers use ions to gate electronic currents and record biological reactions in the intracellular and extracellular space 2, 3, 9, 10, 11, 12, 13, 14, 15, 16. Organic polymers with mixed electronic and ionic conductivity integrated in electrodes and electrochemical transistors transduce ionic to electronic currents and amplify small biological signals3, 17, 18, 19, 20, 21, 22 In addition, organic iontronics locally deliver ions and neurotransmitters in the extracellular space to affect cell and tissue function 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%